Development of chitosan-based adsorbents for removal of reactive Azo Dyes from Aqueous solution. - H. Hameed, Bassim; Ahmad, Abdul Latif (Universiti Sains Malaysia, 2008)

(untitled)
The adsorption of reactive blue 19 (RB19), reactive orange 16 (R016) and reactive black 5 (RB5) on cross-linked chitosan/oil palm ash composite beads was studied in batch and column modes of operation.